Could 5G Technology Be the Cause of COVID-19? - Omar Alani; Ahmed Y. Qasim; Laith Al-Jobouri (Iraqi Journal of Industrial Research)
The burning of 5G sites across the UK in April 2020 has shocked the scientific and industrial society in the UK. The UK's mobile networks have reported 20 cases of masts being targeted in suspected arson attacks over the Easter weekend [1]. The attacks have been driven by conspiracy theories, which claim that the deployment of 5G networks has caused or helped accelerating the spread of COVID-19. But scientists say the connection between COVID-19 and 5G is a "complete nonsense" and biologically impossible. This article discusses the claims about 5G technology and its link to COVID-19 and will make a conclusion whether conspiracy theories have any ground. Our fact checking investigation lead to the conclusion that any claims connecting this technology to the pandemic are false. Inversely, the huge capabilities offered by 5G especially with IoT and AI that could be used to revolutionize the healthcare sector by providing better assistance to the frontline staff, and facilitating improved virus tracking, patient monitoring, data collection, and analysis.